FILM DOCTOR STRANGE IN THE MULTIVERSE OF MADNESS (2022) SEBAGAI BUDAYA POPULER: SEBUAH PERSPEKTIF PENONTON INDONESIA - Rifka Pratama (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2022)
CNBC Indonesia revealed that until July 2020 there were 11 million Indonesian moviegoers who contributed approximately a total of 486 billion to the selling of the Avengers: End Game film tickets. The most recent Marvel Studios film, Doctor Strange in the Multiverse of Madness, starting from May 11 to 15, 2022 grossed 15.7 billion dollars in the Indonesian market. The euphoria of the Indonesian moviegoers about these two films continues in various expressions. It is reflected in many conversations on social media. The mass production of the MCU film merchandise also indicates the wave of euphoria. Film industry has long been closely correlated with the constructs of popular culture. Commercialism, the mass acceptance, and the euphoria throughout the film release reflect the manifestations of popular culture. This article discusses the indicators suggesting that Doctor Strange in the Multiverse of Madness is a product of popular culture in Indonesia. Among the existing indicators are its success in targeting the Indonesian moviegoers through the media, commercialism, and the presence of Indonesian public euphoria.